Healthy Living Behaviors of University Students and Factors Affecting It - KAPLAN, Betül; AYDIN, Neriman (Göbeklitepe Medical Science Journal, 2022)
The youth period, which is included in the university period, is an interim period in which the behaviors of the individual who come out of childhood are not clearly settled, giving her a character and enabling her to reach adulthood. In this transition period, the communication of the young person with the society, her psycho-social and socio-economic status, the place where she stays during education are very important for young people and play a big role in shaping their personality. This research was conducted in order to determine the healthy life behaviors of students and the factors affecting it. The study is a descriptive type of research and the universe of the study was made up of students studying at Hasan Kalyoncu University in the academic year 2013-2014 (1597) and a sample of 640 students who participated in the study. The data were collected using the questionnaire used in the “Youth Risk Behavior Survey” developed by the researchers (Socio-Demographic (25 questions), Risky health behaviors (59 questions), Health service use (6 questions) were used. The data; analyzed using frequency distributions and chi-square test. Results: 52.8% of the students participating in the research were female and 47.2% were male. While 41.2% of the students reside with their families during their education, the rate of students staying at home alone is 10.4%. The rate of students who evaluated their general health status as good is 44.3%. Conclusion: As a result of our study, it can be recommended to add healthy life lessons to the curriculum and organize courses and seminars on this subject in order to increase students’ awareness of healthy life and to lead a healthier life in the future.